Reconstruction in Syria: Challenges and policy options for the EU and its member states - Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2020)
Siyria's civil war has long since been decided in favour of the regime. There is no prospect of a negotiated settlement, reconciliation or lasting stabilisation. Syria faces enormous challenges, well beyond the rebuilding of infrastructure and housing. It will also need assistance to restart its economy, stabilise its currency and renew its public services, in particular education, health, electricity and water. The funds required for comprehensive reconstruction are extremely unlikely to become available, given the attitude of the Syrian leadership, the economic ramifications of the Covid-19 pandemic, and the geopolitical interests of regional and global powers. Nor are resources likely to be deployed in line with the needs of the population. The EU and its member states have made engagement in Syria's reconstruction conditional on viable steps towards a negotiated conflict settlement and a political opening. They should adapt their approach to align better with the current realities and challenges on the ground. That means in particular targeting humanitarian aid more effectively, dismantling certain sectoral sanctions and supporting the rehabilitation of basic infrastructure - even in areas controlled by the Syrian government. This would represent a more effective contribution to improving living conditions and avoiding further erosion of public services. Lasting stabilisation will require fundamental reforms. In this vein, Brussels should spell out its 'more for more' approach. Europe should refrain from normalising relations with the top leaders of the Assad regime and instead step up its support for prosecution of war crimes, grave human rights violations and the use of internationally banned weapons.
Keywords: 320; Nachkonfliktphase; Außenpolitische Strategie; Politische Konditionalität; Außenpolitische Neuorientierung; Vorschlag/Initiative; Internationaler Akteur; Außenpolitische Interessen; Golfstaaten; Übergang zwischen politischen Systemen